Muscular dystrophy-associated SUN1 and SUN2 variants disrupt nuclear-cytoskeletal connections and myonuclear organization - Meinke, Peter; Mattioli, Elisabetta; Haque, Farhana; Antoku, Susumu; Columbaro, Marta; Straatman, Kees R; Worman, Howard J; Gundersen, Gregg G; Lattanzi, Giovanna; Wehnert, Manfred; Shackleton, Sue (PLoS genetics, 2014)
Proteins of the nuclear envelope (NE) are associated with a range of inherited disorders, most commonly involving muscular dystrophy and cardiomyopathy, as exemplified by Emery-Dreifuss muscular dystrophy (EDMD). EDMD is both genetically and phenotypically variable, and some evidence of modifier genes has been reported. Six genes have so far been linked to EDMD, four encoding proteins associated with the LINC complex that connects the nucleus to the cytoskeleton. However, 50% of patients have no identifiable mutations in these genes. Using a candidate approach, we have identified putative disease-causing variants in the SUN1 and SUN2 genes, also encoding LINC complex components, in patients with EDMD and related myopathies. Our data also suggest that SUN1 and SUN2 can act as disease modifier genes in individuals with co-segregating mutations in other EDMD genes. Five SUN1/SUN2 variants examined impaired rearward nuclear repositioning in fibroblasts, confirming defective LINC complex function in nuclear-cytoskeletal coupling. Furthermore, myotubes from a patient carrying compound heterozygous SUN1 mutations displayed gross defects in myonuclear organization. This was accompanied by loss of recruitment of centrosomal marker, pericentrin, to the NE and impaired microtubule nucleation at the NE, events that are required for correct myonuclear arrangement. These defects were recapitulated in C2C12 myotubes expressing exogenous SUN1 variants, demonstrating a direct link between SUN1 mutation and impairment of nuclear-microtubule coupling and myonuclear positioning. Our findings strongly support an important role for SUN1 and SUN2 in muscle disease pathogenesis and support the hypothesis that defects in the LINC complex contribute to disease pathology through disruption of nuclear-microtubule association, resulting in defective myonuclear positioning.